1998
DOI: 10.1164/ajrccm.158.6.9804011
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 and Transforming Growth Factor- β Promoter Polymorphisms in Allergies and Asthma

Abstract: Interleukin-10 (IL-10) and transforming growth factor beta (TGF-beta) are inhibitory for B and T cells, IgE production, and mast cell proliferation, and they induce apoptosis in eosinophils. These cytokines are therefore candidate genes which could contribute to the development of asthma or allergies. We investigated the hypothesis that polymorphic nucleotides within the IL-10 and TGF-beta gene promoters would link to the expression of allergies and asthma. DNA taken from families with an asthmatic proband was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
142
4
8

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(163 citation statements)
references
References 32 publications
9
142
4
8
Order By: Relevance
“…One of these SNP associations has been previously reported by Hobbs et al [1998], who found higher IgE levels associated with the -571C/A (-627 C/A in our report) variant in 97 wild type (C/C) 34 heterozygotes (C/A) and 13 homozygotes (A/A) with asthma.…”
Section: Discussionsupporting
confidence: 76%
“…One of these SNP associations has been previously reported by Hobbs et al [1998], who found higher IgE levels associated with the -571C/A (-627 C/A in our report) variant in 97 wild type (C/C) 34 heterozygotes (C/A) and 13 homozygotes (A/A) with asthma.…”
Section: Discussionsupporting
confidence: 76%
“…The region including the Sp1/Sp3 site and adjoining polymorphism functions as a transcriptional repressor, and the Cto-A base exchange relieves the repression mediated by Sp1 [19]. We demonstrated that the A allele was associated with elevated total serum IgE in subjects heterozygotic or homozygotic for this base exchange [20]. In addition, this polymorphism has also been linked with increased severity of a number of diseases including asthma, rheumatoid arthritis, systemic lupus erythromatosus (SLE) and inflammatory bowel disease [21][22][23][24], and is associated with changes in tumorigenesis and transplantation tolerance [25] and rapid progression to AIDS in individuals infected with HIV [26].…”
Section: Introductionmentioning
confidence: 81%
“…Support for altered homeostasis in Th2 diseases finds credence in studies of mutations associated with these conditions. Allergic disease-linked polymorphisms of the IL-10 promoter, the IL-4 promoter, and the IL-4R ␣-chain have been noted, as well as polymorphisms of Fc⑀RI ␤ (27,13,14,(41)(42)(43)(44)(45)(46). It is possible that such genetic changes may prevent Th2-mediated regulation of mast cell survival and/or Fc⑀RI regulation, though such effects are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies from the laboratories of Rennick and Thompson-Snipes (24 -26) have demonstrated the growth-promoting activities of IL-10 on mouse mast cells and their progenitors. With the recent report of atopy-related polymorphisms in the human IL-10 promoter (27), the literature indicates that a full understanding of IL-10 effects on mast cell biology is clinically relevant but incomplete.…”
Section: Il-10 Inhibits Fc⑀ri Expression In Mouse Mastmentioning
confidence: 99%